2015
DOI: 10.1016/j.molp.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis RING Domain Protein BOI Inhibits Flowering via CO-dependent and CO-independent Mechanisms

Abstract: BOTRYTIS SUSCEPTIBLE1 INTERACTOR (BOI) and its three homologs (BOIs) are RING domain-containing proteins that repress flowering. Here, we investigated how BOIs repress flowering. Genetic analysis of the boiQ quadruple mutant indicates that BOIs repress flowering mainly through FLOWERING LOCUS T (FT). BOIs repress the expression of FT by CONSTANS (CO)-dependent and -independent mechanisms: in the CO-dependent mechanism, BOIs bind to CO, inhibit the targeting of CO to the FT locus, and thus repress the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 80 publications
(110 reference statements)
2
16
0
Order By: Relevance
“…Indeed, CO transcriptional activity is repressed by RUP2, and this effect is detectable at the level of reduced FT expression, FT promoter activity in transient reporter assays, and CO association with the FT promoter in ChIP assays. Interestingly, several CO-interacting proteins were described recently as negative regulators of CO transcriptional activity, acting through recruitment of TOPLESS repressor proteins or through inhibition of CO binding to target genes (Wang et al 2014(Wang et al , 2016Nguyen et al 2015;Zhang et al 2015;Graeff et al 2016;Xu et al 2016;Ordonez-Herrera et al 2018), the latter of which is similar to our findings for RUP2 activity. It is interesting to note that RUP2 binds to the N-terminal part of CO, which is comprised of two tandem B-box domains.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, CO transcriptional activity is repressed by RUP2, and this effect is detectable at the level of reduced FT expression, FT promoter activity in transient reporter assays, and CO association with the FT promoter in ChIP assays. Interestingly, several CO-interacting proteins were described recently as negative regulators of CO transcriptional activity, acting through recruitment of TOPLESS repressor proteins or through inhibition of CO binding to target genes (Wang et al 2014(Wang et al , 2016Nguyen et al 2015;Zhang et al 2015;Graeff et al 2016;Xu et al 2016;Ordonez-Herrera et al 2018), the latter of which is similar to our findings for RUP2 activity. It is interesting to note that RUP2 binds to the N-terminal part of CO, which is comprised of two tandem B-box domains.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, GalvĂŁo et al (2012) showed that GA regulate flowering through controlling the expression of FT, TSF, and SPLs in a day length-specific manner. Additionally, BOTRYTIS SUSCEPTIBLE1 INTERACTORs (a group of interacting partners of DELLA proteins) interact with CO, which inhibit CO to target FT (Nguyen et al, 2015). However, the exact molecular mechanisms underlying interactions of the photoperiod and GA pathways remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that the photoperiod and GA pathways coordinate to modulate flowering under LDs Porri et al, 2012;Reeves and Coupland, 2001;Hou et al, 2014;Nguyen et al, 2015). Very recently, Xu et al (2016) reported that DELLA proteins physically interact with CO, indicating a direct association between the photoperiod and GA pathways.…”
mentioning
confidence: 99%
“…The expression profile of REPRESSOR OF GA1-3 protein, a member of the DELLA protein family, diurnally oscillates with a trough in the afternoon when CO induces FT expression. GA also regulates CO function through BOTRYTIS SUSCEPTIBLE1 INTERACTOR (BOI; Nguyen et al, 2015). BOI interacts with CO but it does not affect CO protein stability; instead, it influences the DNA binding ability of CO to the FT promoter.…”
Section: Transcriptional Regulation Of Ftmentioning
confidence: 99%